Using Juxtaposing Pictures in Improving Descriptive Writing Skill of the Second Year Students of SMAN 3 Enrekang - Risan, Rahmad; G, Hasriani (Universitas Negeri Semarang, 2019)
The objective of the research was to find out whether or not the use of juxtaposing pictures can improve the students’ writing ability especially in writing description. The researchers applied a pre-experimental method with one group pre-test and one group post-test design. The subject of the research was the second year students of SMAN 3 Enrekang in academic year 2017-2018. The sample consisted of 32 students of XI IPA 1. The data were collected through writing test (pretest and post-test). To find out the effectiveness of juxtaposing pictures in improving writing ability, the researcher applied t-test analysis. The result of the analysis showed that there was a significant difference between pre-test and post-test. The value of t-test (9.09) was greater than the t-table (2.039) and degree of freedom (df) = 31. It is concluded that juxtaposing pictures is effective in improving the students’ writing ability in writing description.